A high-resolution wide-field radio survey of M51 - Rampadarath, H.; Morgan, J.; Soria, R.; Tingay, Steven; Reynolds, C.; Argo, M.; Dumas, G. (Oxford University Press, 2015)
We present the highest resolution, wide-field radio survey of a nearby face-on star-forming galaxy to date. The multiphase centre technique is used to survey the entire disc of M51 (77 arcmin2) at a maximum resolution of 5 mas on a single 8 h pointing with the European Very Long Baseline Interferometry (VLBI) Network at 18 cm. In total, 7 billion pixels were imaged using 192 phase centres that resulted in the detection of six sources: the Seyfert nucleus, the supernova SN 2011dh, and four background AGNs. Using the wealth of archival data available in the radio (Multi-Element Radio Linked Interferometer Network and the Very Large Array), optical (Hubble Space Telescope) and X-rays (Chandra) the properties of the individual sources were investigated in detail. The combined multiwavelength observations reveal a very complex and puzzling core region that includes a low-luminosity parsec scale core-jet structure typical of AGNs, with evidence for a lateral shift corresponding to 0.27c. Furthermore, there is evidence for a fossil radio hotspot located 1.44 kpc from the Seyfert nucleus that may have resulted from a previous ejection cycle. Our study provides measures of the supernova and star formation rates that are comparable to independent studies at other wavelengths, and places further limits on the radio and X-ray luminosity evolution of the supernovae SN 1994I, SN 2005cs and SN 2011dh. The radio images of background AGN reveal complex morphologies that are indicative of powerful radio galaxies, and confirmed via the X-ray and optical properties.